Guanylate-binding protein-5 is involved in inflammasome activation by bacterial DNA but only the cooperation of multiple GBPs accounts for control of Brucella abortus infection - Marinho, Fabio V.; Brito, Camila; de Araujo, Ana Carolina V. S. C.; Oliveira, Sergio C. (Frontiers in Immunology, 2024)
Guanylate-binding proteins (GBPs) are produced in response to pro-inflammatory signals, mainly interferons. The most studied cluster of GBPs in mice is on chromosome 3. It comprises the genes for GBP1-to-3, GBP5 and GBP7. In humans, all GBPs are present in a single cluster on chromosome 1. Brucella abortus is a Gram-negative bacterium known to cause brucellosis, a debilitating disease that affects both humans and animals. Our group demonstrated previously that GBPs present on murine chromosome 3 (GBPchr3) is important to disrupt Brucella-containing vacuole and GBP5 itself is important to Brucella intracellular LPS recognition. In this work, we investigated further the role of GBPs during B. abortus infection. We observed that all GBPs from murine chromosome 3 are significantly upregulated in response to B. abortus infection in mouse bone marrow-derived macrophages. Of note, GBP5 presents the highest expression level in all time points evaluated. However, only GBPchr3 -/-cells presented increased bacterial burden compared to wild-type macrophages. Brucella DNA is an important Pathogen-Associated Molecular Pattern that could be available for inflammasome activation after BCV disruption mediated by GBPs. In this regard, we observed reduced IL-1β production in the absence of GBP2 or GBP5, as well as in GBPchr3 -/-murine macrophages. Similar result was showed by THP-1 macrophages with downregulation of GBP2 and GBP5 mediated by siRNA. Furthermore, significant reduction on caspase-1 p20 levels, LDH release and Gasdermin-D conversion into its mature form (p30 N-terminal subunit) was observed only in GBPchr3 -/-macrophages. In an in vivo perspective, we found that GBPchr3 -/-mice had increased B. abortus burden and higher number of granulomas per area of liver tissue, indicating increased disease severity. Altogether, these results demonstrate that although GBP5 presents a high expression pattern and is involved in inflammasome activation by bacterial DNA in macrophages, the cooperation of multiple GBPs from murine chromosome 3 is necessary for full control of Brucella abortus infection.